Advances in Vaccine Development for Human Lymphatic Filariasis - Kalyanasundaram, Ramaswamy (Trends Parasitol, 2019)
According to the World Health Organization, currently, over 880 million people are at risk of acquiring the lymphatic filariasis (LF) infection in over 52 countries worldwide. Current approaches to control LF by 2020 are reaching short of its anticipated goal. Several studies suggest the existence of protective immunity against LF in the human. Thus, it is possible to develop a prophylactic vaccine against LF infections in the human. Several potential vaccine candidates were identified and tested for their vaccine potential against LF. Preclinical studies to date suggest that it is possible to develop a prophylactic vaccine against LF. Much work needs to be done, but it is clear that a prophylactic vaccine combined with targeted chemotherapy is critically required for eliminating LF worldwide.